2011
DOI: 10.1017/s0007114511005484
|View full text |Cite
|
Sign up to set email alerts
|

Oxidised fish oil does not influence established markers of oxidative stress in healthy human subjects: a randomised controlled trial

Abstract: Intake of fish oil reduces the risk of CHD and CHD deaths. Marine n-3 fatty acids (FA) are susceptible to oxidation, but to our knowledge, the health effects of intake of oxidised fish oil have not previously been investigated in human subjects. The aim of the present study was to investigate markers of oxidative stress, lipid peroxidation and inflammation, and the level of plasma n-3 FA after intake of oxidised fish oil. In a double-blinded randomised controlled study, healthy subjects (aged 18-50 years, n 54… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
77
5
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(90 citation statements)
references
References 84 publications
6
77
5
2
Order By: Relevance
“…1 Dr. Naegele expressed concern regarding the safety of omega-3 fatty acids based on the numbers of mortality cases in the omega-3 fatty acid and placebo treatment arms. Dr. Naegele postulated that the long term cumulative effect of omega-3 fatty acids exposure may be harmful due to “lipid peroxidation” following “gradual accumulation within biological membranes.” Although, at the present time, the effects of omega-3 fatty acids on lipid peroxidation and mitochondrial glucose utilization remain unclear, 2 we do not find supportive evidence that indicate harmful effects from omega-3 fatty acids in our study. First, our study was not powered to evaluate for the outcome of patient mortality and given the small numbers of deaths (3 and 8 cases in placebo and omega-3 fatty acids groups, respectively, P=0.22), no conclusive results can be drawn regarding patient mortality.…”
Section: Lettercontrasting
confidence: 97%
“…1 Dr. Naegele expressed concern regarding the safety of omega-3 fatty acids based on the numbers of mortality cases in the omega-3 fatty acid and placebo treatment arms. Dr. Naegele postulated that the long term cumulative effect of omega-3 fatty acids exposure may be harmful due to “lipid peroxidation” following “gradual accumulation within biological membranes.” Although, at the present time, the effects of omega-3 fatty acids on lipid peroxidation and mitochondrial glucose utilization remain unclear, 2 we do not find supportive evidence that indicate harmful effects from omega-3 fatty acids in our study. First, our study was not powered to evaluate for the outcome of patient mortality and given the small numbers of deaths (3 and 8 cases in placebo and omega-3 fatty acids groups, respectively, P=0.22), no conclusive results can be drawn regarding patient mortality.…”
Section: Lettercontrasting
confidence: 97%
“…Recent studies have reported elevated peroxide levels in commercialised fish oil capsules, which have led to some concern that regular consumption of oxidised marine oils may negatively affect human health ( 16 21 ) . In a previous study, we did not observe any changes in fasting plasma LC n -3 FA levels, lipids or several other oxidative stress markers after 7 weeks of consumption of oxidised compared with non-oxidised fish oil ( 22 ) . However, another study reported that the intake of less oxidised n -3 FA supplements for 30 d reduced blood lipids and blood pressure compared with highly oxidised LC n -3 FA supplements ( 23 ) .…”
mentioning
confidence: 52%
“…The limits are also below oxidation levels seen in other ingredients or food items available to consumers, as well as the maximum limits for oxidation for seed and plant oils that are also sensitive to oxidation 6, 7 . In addition to monitoring ingredient and product quality, the accurate measurement of fatty acid content and oxidative status is fundamental to permitting the proper assessment of the biological relevance of different types of omega-3 LCPUFA-containing oils, as well as the dependence of the biological effect on the concentration and type of any oxidation products that may be present in oils, in combination with dose- and time-dependent exposure 810 .…”
Section: Introductionmentioning
confidence: 99%